Assessing Local Turbulence Strength from a Time Series. (31st May 2010) - Humi, Mayer
Abstract : We study the possible link between "local turbulence strength" in a flow which is represented by a finite time series and a "chaotic invariant", namely, the leading Lyaponuv exponent that characterizes this series. To validate a conjecture about this link, we analyze several time series of measurements taken by a plane flying at constant height in the upper troposphere. For each of these time series we estimate the leading Lyaponuv exponent which we then correlate with the structure constants for the temperature. In addition, we introduce a quantitative technique to educe the scale contents of the flow and a methodology to validate its spectrum.